Mystical science and practical religion muslim, hindu, and sikh discourse on science and technology - Cimino, Richard P. (Lexington Books, 2014)
Mystical Science and Practical Religion examines the religious discourse employed by Muslim, Hindu, and Sikh applied science professionals and students, mainly engineers and Information Technology (IT) workers. Although applied scientists, especially immigrants to the United States, have shown high rates of religiosity, there have been few studies of this subject. Based on interviews with forty-five professionals and students, Cimino finds that although they are from different faiths, these applied scientists share a common discourse that blends religion and science. They each view their religions as the "most scientific." Their work and study reshapes how they practice and conceptualize their faiths, though not in the expected directions of secularization and fundamentalism. This book provides a unique look at how the much contested fields of science and religion interact in real life.